The Role of Organizational Culture in Predicting Work Performance on Company Performance of Palm Oil Companies in Indonesia - Purba, Mohd. Nawi; MD Isa, Mohd. Azwardi (International Journal of Entrepreneurship and Business Management, 2024)
This study examines the relationship between organizational culture and work performance through the competence of managers in palm oil companies in Indonesia. The sample of this study were all managers of private oil palm plantation companies, so the number of samples studied was 100 respondents, and data analysis techniques using analysis with Partial Least Square (PLS). The results of the study  that external adaptation gives a positive and significant impact on work performance, external adaptation gives a positive and significant impact on company performance internal integration  does not give a positive and insignificant impact on Work performance  Internal Integration (X2) does not give a positive and significant impact on the Company Performance, Basic Assumptions (X3) give a positive and significant impression on Work performance (Z1), Basic Assumptions (X3) do not give an impression positive and not significant to the Company Performance (Y), Self-Esteem (Z2) gives a positive and significant impression to the Company Performance  Work performance as a gap modifier has a positive and significant effect in showing the effect of External Adaptation  on the Company Performance , Work performance (Z1) as a gap modifier does not give a positive effect and is not significant in showing the effect of Internal Integration on Company Performance (Y), Work performance as a modifier of the gap has a positive and significant effect in showing the impression of the Basic Assumptions on Company Performance, Self-Esteem (Z2) as a simplification of does not have a positive and insignificant impression of the Company Performance.